Liolaemus goetschi : predation - Avila, Luciano Javier (2011)
Liolaemus goetschi is an oviparous and insectivorous, medium-sized lizard (max. SVL = 73 mm) inhabiting the arid landscape of Monte Desert in northern Patagonia, Argentina. Its geographic distribution ranges through a narrow strip in northwestern Rio Negro Province along the boundary with Neuquén Province (Nori et al. 2010. Check List 6:3–4). To our knowledge, no studies are available on the biology of this species, including its natural predators. Here we report an observation of Philodryas psammophidea predation on L. goetschi. Philodryas psammophidea is an uncommon snake, with a large geographic distribution within Monte and Chacoan environments of Bolivia, Paraguay, and Argentina.